2014
DOI: 10.1161/circgenetics.114.000623
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genes Encoding for the Transient Outward Current (Ito) Identifies the KCND2 Gene as a Cause of J-Wave Syndrome Associated With Sudden Cardiac Death

Abstract: 782J -wave syndromes refer to a spectrum of ECG observations characterized by early ST-segment takeoff from the terminal QRS or J-point.1,2 The associated QRS segment may demonstrate terminal slurring, representing a J wave concealed within the QRS complex, or present a more distinctly visible notch representing a J wave. Brugada syndrome is the most well-characterized J-wave syndrome, both in terms of clinical and genetic features. Alternative patterns of J-wave syndromes have long been recognized, commonly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 34 publications
(32 reference statements)
1
39
0
Order By: Relevance
“…The J wave syndromes and IVF have also been associated with gain of function mutations in the transient outward potassium current (I to ). 17, 3239 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The J wave syndromes and IVF have also been associated with gain of function mutations in the transient outward potassium current (I to ). 17, 3239 …”
Section: Discussionmentioning
confidence: 99%
“…4, 12 Higher intrinsic levels of I to were shown to account for the greater sensitivity of the inferior LV wall to development of VT/VF in the setting or ERS. 4 The outward shift in the balance of currents was attributable to mutations in genes causing a gain of function in IK-ATP ( KCNJ8 and ABCC9 ) or I to ( KCNE5 mutation and rare polymorphism in DPP10 ) 1317 or loss of function in I Ca ( CACNA1C, CACNB2 and CACNA2D1 ) 18, 19 or I Na ( SCN5A and SCN10A ). 20, 21 The goal of a pharmacologic approach to therapy should therefore be to produce an inward shift in the balance of current flowing during the early phases of the LV epicardial AP.…”
Section: Introductionmentioning
confidence: 99%
“…Gain-of-function mutations in KCND3 have been implicated in BrS [40] with an enhanced I to current gradient within the right ventricle where KCND3 expression is the highest. Gain-of-function mutations in KCND2 have been associated with J-wave syndromes, including BrS [41]. KCNE3 , encoding MiRP2, decreases the I to current by interacting with the channel Kv4.3 and results in increased I to magnitude and density in the human heart, which could underlie the pathogenesis of BrS-pattern ECG [42].…”
Section: Brugada Syndromementioning
confidence: 99%
“…Recently, detection of a KCND2 (Kv4.2) gene mutation in a patient with J-wave syndrome led to the suggestion that the Kv4.2 subunit might also contribute to the generation of I to,f in human heart (Perrin et al, 2014). The significance of this finding remains to be clarified since multiple investigators have shown that this gene is not expressed at significant levels in the human heart (Bertaso et al, 2002; Dixon et al, 1996; Gaborit et al, 2007; Isbrandt et al, 2000; Rosati et al, 2008; Zhu et al, 1999).…”
Section: Molecular Basis Of Ito and Its Transmural Gradient Of Expresmentioning
confidence: 99%